1998
DOI: 10.1038/sj.bjp.0701776
|View full text |Cite
|
Sign up to set email alerts
|

Serine‐O‐sulphate transport by the human glutamate transporter, EAAT2

Abstract: 1 Expression of the recombinant human excitatory amino aid transporters, EAAT1 and EAAT2, in Xenopus laevis oocytes allows electrogenic transport to be studied under voltage clamp conditions. 2 We have investigated the transport of the pharmacological substrate, L-serine-O-sulphate transport by EAAT1 and EAAT2. The EC 50 values for L-serine-O-sulphate transport by EAAT2 showed a steep voltage-dependence, increasing from 152+11 mM at 7100 mV to 1930+160 mM at 0 mV. In contrast to EAAT2, EC 50 values for L-serin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…This Gly for Ser difference has previously been investigated using the rat equivalent of human EAAT2 (19), and it was found that the S440G mutation reduced the affinity of the EAAT2-selective blocker, dihydrokainate, and also allowed Li ϩ to drive transport. Two previous studies have also demonstrated that the affinity of Na ϩ for the transporter is dependent upon the substrate being transported (20,21), which provided hints of a link between substrate/blocker interactions and Na ϩ binding. These observations provide us with the tools to investigate the specificity of the coupling process and why compounds such as MPDC and 4MG are very good substrates for EAAT1 and are either blockers or poor substrates of A higher L-glutamate concentration than MPDC and 4MG was used because of its higher EC 50 in Li ϩ (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This Gly for Ser difference has previously been investigated using the rat equivalent of human EAAT2 (19), and it was found that the S440G mutation reduced the affinity of the EAAT2-selective blocker, dihydrokainate, and also allowed Li ϩ to drive transport. Two previous studies have also demonstrated that the affinity of Na ϩ for the transporter is dependent upon the substrate being transported (20,21), which provided hints of a link between substrate/blocker interactions and Na ϩ binding. These observations provide us with the tools to investigate the specificity of the coupling process and why compounds such as MPDC and 4MG are very good substrates for EAAT1 and are either blockers or poor substrates of A higher L-glutamate concentration than MPDC and 4MG was used because of its higher EC 50 in Li ϩ (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The first molecular probe, L-serine-O-sulfate, is a substrate for transporters which displays a difference in affinity (8,16,23). Chloride permeability, the second molecular probe, is markedly different between EAAT1 transport of D-aspartate and EAAT2 transport of D-aspartate (17) and was employed to delineate further the differences in EAAT1 and EAAT2 related to the pore of the transporter.…”
Section: Discussionmentioning
confidence: 99%
“…L-Serine-O-sulfate is a substrate for both EAAT1 and EAAT2, but it is a less potent substrate on EAAT2 than EAAT1. In addition, the EC 50 2 values for L-serine-O-sulfate transport by EAAT2 are steeply voltage-dependent but relatively constant for transport by EAAT1 (16). This difference between EAAT1 and EAAT2 in L-serine-O-sulfate transport is likely to reflect a difference in the structure of the pore of the two transporters.…”
mentioning
confidence: 95%
“…Moreover, L-serine-O-sulfate, L-homocysteate, L-homocysteine sulfinate, L-ibotenate, and L-quisqualate activate metabotropic glutamate receptors (26,119,184,248), and (S)-4-CPG is a Group I metabotropic glutamate receptor antagonist (22). L-serine-O-sulfate also acts as an inhibitor of serine racemase (199) and aspartate aminotransferase (273) as well as an EAAT substrate (278). While Lquisqualate and (S)-4-CPG are the most potent inhibitors of system x c --mediated glutamate uptake, they are less well transported by system x c -than L-ibotenate and noncyclic glutamate analogs.…”
Section: Fig 2 System X Cmentioning
confidence: 99%